Research and extension completed and on-going registered programs database system (RECORDS) - Villa, Frederick T.; Natividad, Arvin N.; Tulod, Razel C. (Linguistics and Culture Review, 2021)
The study designed and developed RECORDS (Research and Extension Completed and On-going Registered programs Database System which will serve as the central storage of data of SLSU Research and Extension offices. The development of the system used VB.Net as a programming language and MySQL as database of the system application to function properly. This research followed the process of developmental research. It was conducted during the school year 2019-2020 at SLSU Campus Lucena The developed software and data base system were evaluated by IT experts, selected members of Research and Extension Council and researchers and extensionists of SLSU. The parameters used in evaluating the developed system were functionality, reliability, usability, efficiency, maintainability, portability and security. The evaluation result showed that the 30 respondents highly accepted the system. Overall rating of the RECORDS evaluation got the average weighted mean of 3.79 with equivalent interpretation of highly acceptable. This implied that, the developed RECORDS (Research and Extension Completed and On-going Registered programs Database System) can be utilized by the SLSU Research and Extension Offices.